Effect of Isolated Vs in-Game Curvilinear Displacements in Multi-Location External Workload Profile. A Case Study in Semi-Professional Basketball Players - Gómez-Carmona C. D; Reina M; Pino-Ortega J; Ibáñez S. J (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
In team sports, linear and non-linear displacements are combined during the game. In this sense, the importance of curvilinear trajectories and their impact on body joints have not been addressed yet. Therefore, the present research aims to: (a) describe the multi-location external workload profile during curvilinear displacements in isolated and in-game conditions, (b) compare the effect of direction and displacement context, and (c) analyse the correlation between impacts and curvilinear performance. Thirteen semi-professional male basketball players were assessed in two tests: (a) isolated (2 directions x 5 repetitions x 6.75-m line) and (b) in-game (10-min 3vs3 small-sided game). To evaluate curvilinear performance and impacts suffered per joints, six WIMU PROTM inertial devices (scapulae, centre of mass, 2x knee, 2x ankle) were placed through a specific integral whole-body vest. Statistical analysis was composed by ANOVA with Bonferroni post-hoc, t-test for independent samples and Pearson correlation coefficient, analysing the effect of magnitude by Cohen’s d and omega partial squared. The key findings indicate that straight displacements presented lower external workload than curvilinear displacements during in-game conditions (p<.01; = 0.47-to-0.50), but no differences were found between left and right directions (p>0.67; d<0.12). In addition, differences were found at lower limb locations in external workload in maximum sprinting during curvilinear displacements, with higher workload at left lower limb in right direction (knee: p<.01, d= -1.35; ankle: p<.01, d= -0.91), and at right lower limb in left direction (knee: p<.01, d= 1.23; ankle: p<.01, d= 0.91). Very high between-subjects variability has been shown in both tests. Besides, a nearly perfect relationship between external workload at different body locations (p<.01; r>0.918) and a high relationship between external workload and centripetal force were found (p<.01; r>0.518). In conclusion, curvilinear displacements should be trained specifically and, in both directions, due to the differences presented with straight displacements, considering the lower limb joints (knee and ankle). Due to the demands during in-game situations represent around 50% of maximum centripetal force and 20-to-40% of maximum external workload, a sprinting test with curvilinear displacements seems to be optimum to detect asymmetries for design training programs to reduce the injury risk in team sports players, specifically in basketball.